Promoting Green Savings Sukuk on Instagram: A Qualitative Analysis of Green Literacy in Investment Platform Instagram Posts - Wahyudi, Setto Lintang Agung; Aprianingsih, Atik (Universitas KH. Abdul Chalim Mojokerto, 2026)
This qualitative study investigates how investment platforms, securities firms, and banks promote green investments on Instagram, specifically examining the communication strategies used for Indonesia's Green Savings Sukuk. Through systematic content analysis of 401 Instagram posts covering green sukuk issuances from November 2019 to March 2025, this research identifies messaging patterns related to green literacy, perceived benefits, subjective norms, and perceived behavioral control. The analysis reveals that investment platforms predominantly emphasize financial benefits and convenience messages, with perceived financial benefits accounting for 744 keyword occurrences compared to only 37 environmental benefit mentions. Within green literacy messaging, financial literacy-related keywords significantly outnumber sustainability literacy-related keywords, suggesting an imbalance in educational messaging. This study demonstrates that despite the substantial role of green literacy in shaping investment attitudes and intentions, current promotional strategies inadequately integrate the environmental and financial knowledge required for informed green investment decisions. The findings highlight a critical gap between industry communication practices and the comprehensive sustainability literacy that Generation Z investors require to bridge their environmental awareness with actual green investment participation.